Nudging for tax compliance: A meta-analysis - Armenak Antinyan; Zareh Asatryan (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Governments increasingly use nudges to improve tax collection. We synthesize the growing literature that evaluates nudging experiments using meta-analytical methods. We find that simple reminders increase the probability of compliance by 2.7 percentage points relative to the baseline where about a quarter of taxpayers are compliant. Nudges that commonly refer to elements of tax morale increase compliance by another 1.4 percentage points. Deterrence nudges, which inform taxpayers about enforcement parameters, increase compliance the most, amounting to an additional 3.2 percentage points increase on top of reminders. Our additional findings highlight the conditions where nudges are more effective, such as their potential when targeting sub-population of late-payers, and also suggest that even this sample of randomized trials may be susceptible to selective reporting of results. Overall, our findings imply that taxpayers are biased by various informational and behavioral constraints, and that nudges can be of some help in overcoming these frictions.
Keywords: C93; D91; H26; 330; Tax compliance; Tax evasion; Randomized control trials; Nudging; Reminders; Tax morale; Deterrence; Meta-analysis; Publication selection bias